Collaborative Leadership Practices and Their Impact on Educational Quality Management - Yulianti, Febi; Rizal, Rizal; Pahriadi, Pahriadi; Aqil, Muhammad; Wilade, Surahman; Lapasere, Sisriawan (Journal of Innovation and Research in Primary Education, 2026)
Collaborative leadership has emerged as a critical approach for enhancing educational quality management, yet its implementation in resource-constrained rural schools remains underexplored. This qualitative descriptive study examined collaborative principal leadership and its role in implementing educational quality management at SD Inpres 3 Tolai, Central Sulawesi, Indonesia. Data were collected through semi-structured interviews with the principal and nine teachers, document analysis, and structured questionnaires, then analyzed using thematic analysis and descriptive statistics. Findings revealed that collaborative leadership achieved 90.2% effectiveness, characterized by participatory decision-making, professional empowerment, trust-building, and institutionalization of Professional Learning Communities. Six major themes emerged: participatory decision-making, empowerment and professional development, trust-building and democratic climate, Professional Learning Communities, adaptive leadership in the digital era, and implementation challenges including time constraints and resource limitations. Teachers unanimously perceived the principal’s leadership as highly collaborative, with 59.4% strongly agreeing and 40.6% agreeing across all measured dimensions. The study demonstrates that collaborative leadership can function effectively in resource-constrained contexts by leveraging relational capital—trust, communication, and shared commitment—to compensate for material limitations. Findings support Collaborative Leadership Theory and Total Quality Management principles, illustrating how distributed decision-making fosters continuous improvement and democratic organizational culture. The research contributes evidence-based insights for strengthening educational leadership capacity in rural Indonesian elementary schools.